(untitled) (Semiárida, 2020)
The objective of this study was to evaluate the variability of B. brevis Nees. Nineteen accessions were collected at different locations of La Pampa and Buenos Aires provinces and characterized in 1992 on the basis of agronomic characters. Accessions were arranged in a randomized complete block design with 3 replications. Analysis of variance and FLSD tests were performed. High variabi-lity (p<0.01) was found for seed yield, weight of 1000 anthecium, days to flowering, plant height, flag leaf length, number of spike-Iets per panicle, and panicle lenght. Significant variability (p<0.05) was also found for dry matter yield, leaf flag width, spikelet length and number of anthecium per panicle. No variability was found for internode lenght, spikelet width, number of anthecium per spikelet, awn length, fresh matter yield, and dry matter percentage. These results showed different levels of variabilily tor the agronomic characters evaluated in B. brevis.